Fresh Produce Handling, Sanitation, and Safety Measures: Citrus - M. Mahovic; Jeffrey Brecht; Steven Sargent; Mark Ritenour; Keith Schneider; Amy Simonne; Jerry Bartz (EDIS, 2003)
This document is FSHN0211, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication: October 2002.